Elite professional football players' perceptions and preferences of pre-match meeting delivery - Travis, P.; Butterworth, A. (International Journal of Performance Analysis in Sport, 2026)
To date, little consideration has been given to the impact on elite athletes of the time at which pre-match meetings are conducted in relation to kick-off. The use of an online survey and follow-up semi-structured interviews explored the perceptions of elite professional football players towards the timing of such meetings. A total of 40 elite professional football players from nine English Football League (EFL) clubs in England completed a semi-structured survey. Additionally, six players completed a semi-structured interview. Three key themes emerged from the inductive analysis of the data: (1) player routines, (2) matchday focus and (3) time to process delivered information. The main finding of the study concludes that players prefer receiving information the day before kick-off. Furthermore, the results highlighted contextual factors previously not discussed in the PA literature such as players` pre-match routines linked to pre-performance anxiety, matchday focus, and the time between pre-match meeting delivery and kick-off, in order to facilitate discussions with coaches on key messages and enable time to process. The findings from the study help strengthen the knowledge coaches, analysts and researchers have on the implications of pre-match delivery to support successful outcomes.